The performance of mechanical anchors in South African mechanized deep level gold mining - Sengani, F.; Zvarivadza, T. (CRC Press, 2022)
Most of South African mechanized and semi-mechanized gold mines in the Witwatersrand basin are operating at depths ranging from 2.7–3 km below the earth surface. Before a tunnel is excavated, the underground stress distribution is uniform (ignoring tectonics) and the magnitude of vertical stress increases proportionally to the depth. But once a tunnel is created, the portion of the strata directly above the tunnel loses its original support and the stress equilibrium is disturbed. The hanging wall starts to sag under the gravitational force. As a result; most of the mines prefer to install mechanical anchors as their reinforcement system within the tunnels, with the aim of improving the stability of the tunnel. This paper aims to evaluate the performance of mechanical anchors in deep level gold mining. Laboratory tensile tests were performance, followed by underground pull tests to determine the performance of mechanical anchors in different conditions. The results obtained from tensile tests have shown that mechanical anchors of 18 mm diameter cable, 4.5 m length, with six strands, can withstand a minimum load of 332 kN and the maximum load of 3441 kN, with a minimum displacement of 98 mm and maximum displacement of 105 mm. Underground pull test results showed similar results or closely related results. Kinematic analysis showed that there were six joint sets around the tunnel, this was confirmed using DIPS software (Stereonet). However, the six joint sets were found to create large wedges along the sidewalls of the excavation, this was confirmed using Un-wedge software.